The Relationship Between State Budget Revenues from Corporate Income Tax and the Amount of Private Investment by Small, Medium and Large Enterprises - Skuza, Joanna (Olsztyn Economic Journal, 2021)
Investing is inherent in the budgetary decisions of legal entities regardless of their size. Macroeconomic, financial and institutional factors affect the environment of investment activity. The article considers one of the elements of the macro environment of enterprises which is the relationship between state budget revenues from corporate income tax and investment outlays of small, medium and large enterprises in the private sector of the national economy. The aim of the study is to identify the relationship between state budget revenues from corporate income tax and the amount of outlays in the private sector of the national economy among enterprises with more than nine employees in Poland in the years 2010-2020 on the basis of data from the Central Statistical Office and reports approved by the Council of Ministers on the implementation of the state budget in the period from 2010 to 2020 contained on the website of the Ministry of Finance. The Pearson correlation analysis method was used to verify the research hypothesis. Based on the obtained value of Pearson’s correlation coefficient, it was found that there is a very strong stochastic positive relationship between state budget income from corporate income tax and investment expenditures in the private sector of the national economy among small, medium and large enterprises.